Effect of the core thickness on the flexural behaviour of polymer foam sandwich structures. (28th August 2020) - Gupta, Yash; Paul V, Varghese; Jacob, Ashish; Mohanty, Akash
Abstract: In this study, the effect of the core thickness of the sandwich composite on its flexural strength was investigated. E-glass fibre reinforced epoxy-based laminates were used as the skin materials whereas a polyurethane foam was used as the core material with varying thickness of 5, 7, and 9 mm. The experimental/theoretical and FEA analysis were carried out. Results indicated that as core thickness increased, the axial face stresses/core shear stresses and total deformation decreased. This improved the composite structural properties. This improvement was accompanied by a minor increase in weight. A good concurrence was observed between theoretical and FEA results. These results allow us to compare and select optimum parameters for aerospace applications.